IMPLEMENTASI ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION (AATHP) DALAM MEMINIMALISIR KASUS KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU - Najla Syafura Syafawani Sagiri; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research focuses on the implementation of the ASEAN Agreement on Transboundary Haze Pollution (AATHP) in controlling the forest and land fire cases that often occurs in its member countries, one of them is Indonesia. Indonesia is a country with the largest number of forests in ASEAN, including the Riau Province. The AATHP was signed by ASEAN member countries on 2002, and Indonesia ratified the agreement on 2014. The AATHP contains 32 articles which regulate the objectives, principles, obligations, monitoring, assessment, prevention, technical and financial cooperation.This research uses the perspective of Green Theory and International Environmental Regime Theory. Green Theory assumed that the division between domestic and international politics could occur because of the national boundaries that do not coincide with the ecosystem, and this can be a collective transboundary and global environmental problem. Then, the environmental regime emerged because of human activities that destroy nature, thus the raise of the environmental regime is expected to eradicate environmental problems in the regional and global scope. This research was conducted using qualitative methods with descriptive analysis. Data collection techniques were carried out through secondary data sources, such as previous research, journals, and other library sources.This research shows that there are differences in the number of hotspots and the area of forest fires before and after Indonesia ratified AATHP. There are efforts made by the Indonesian government, especially the Riau provincial government in preventing and overcoming forest and land fires in accordance with the contents of the AATHP. The results of these efforts can be seen from the change in numbers after Indonesia ratified and implemented AATHP. Keywords: Green Theory, International Environmental Regime, Transboundary Haze, Forest and Land Fire, AATHP.